Vulnerabilty Area of Filariasis Based on Risk Factors with Geographic Information System Approach - Marko Ferdian Salim (Jurnal Sistem Informasi Kesehatan Masyarakat, 2016)
Background: Filariasis is a parasitic disease caused by microscopic, thread-like worms (Wuchereria bancrofti, Brugia malayi, and Brugia timori) which transmitted by mosquito bites. WHO records more than 1.4 billion of world population settle in areas with filariasis infection risk which are spread in 73 nations included Indonesia. Filariasis in Indonesia spread in 418 districts while 235 districts are stated as endemic areas with 14.932 cases. In West Sumatera, the Agam District becomes one of filariasis endemic areas with the highest rate with cases prevalence to 12.63 per 100.000. The environment condition of the Agam District situates the area with mountains, plains, rivers, lakes, farms, and rice fields.Objective: The study aimed to implement the use of Geographic Information System for vulnerability area mapping based on risk factors of filariasis in Agam District.Methods: The study is analytic observational, designed with case control study. Odds Ratio (OR) used to find out risk factor estimation of filariasis prevalence. This study involves 36 cases with 36 controls summed to 72 samples. Analysis of the data was used univariate, bivariate, multivariate and vulnerability area analysis spatially.Results: Geographic Information System (GIS) can be used to determine the level of vulnerability area of filariasis in Agam District. Statistical data such as low education (OR: 4.52), low knowledge (OR: 4.14), profession (farmer, labour, and fisherman) (OR: 4.38), and low income (OR: 4.43) along with that the behaviours of community such as high outdoor activities at night (OR: 3.75) and reservoir animal farming (OR: 3.57) are recorded as filariasis risk factors. Environment condition shows that plantation area (OR: 19.46), where mosquito breeding is commonly located, is the risk factor too. Based on multivariate analysis, the filariasis risk factor in the Agam District is the existence of plantation area (OR: 19.46) as well. The research found that Culex (67.26%), Aedes (18.06%), Armigeres (14.19%), and Anopheles (0.48%) were vectors of the disease. The clustering of filariasis cases was located in Subang – Subang and Muaro Putuih. The vulnerability zones found in Agam District such as Sub-district Tanjung Mutiara, Lubuk Basung, IV Nagari, Palembayan, Palupuh, Baso and IV Koto.Conclusions: The risk factors of filariasis in Agam were low education, low knowledge, profession (farmer, labour, and fisherman), low income, high outdoor activities at night, reservoir animal farming, and plantations area as mosquito breeding sites approximately 200 metres from residence. Filaria vector types in Agam such as Culex, Armigeres, Aedes and Anopheles. The vulnerability area and clustering of filariasis known by using Geographic Information System.Keywords: Geographic Information System (GIS), Filariasis, Risk factor, Vulnerability, Agam District.